Possible correlations between athletic training and the degree of strain placed upon the body's apparatuses and systems - Drosescu Paula; Puni Alexandru Rares (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
The present study is included among those situated at the border between sports medicine and athletic training, being aimed at optimizing the volleyball training. The study is based on the analysis of the results achieved by "Penicilina Iasi" volleyball team in the athletic season 2011-2102. This paper aims to analyze the level of competition-related stress and the degree to which various apparatuses and systems of the body are overworked by using the DDFAO test. The DDFAO (Dépistageet Diagnostic FonctionnelAssisté par Ordinateur) is a relatively new method in Europe, and is based on scanning the body and recording its bio-conductibility. The test is noninvasive and quick, offering a view on what goes on in the body at a cellular level. The test is conducted through the means of electrodes. In the data we present this time, we would like to identify whether there is a possible correlation between the athletic training and the overworking of the body's apparatuses and systems during effort. The subjects of our experiment are the players from the "Penicilina Iasi" volleyball team, aged between 18 and 46 years old. The tests were conducted in the "Alternative" medical practice office in Iasi and were carried out at 3 different times: after the competition break, at the return from training camp and before the peak of the competition season. The tests have shown a normal level of stress after the first test. The second and third test have shown a more important level of stress on the body's apparatuses and systems, which can be correlated with a lower level of performance during that time.